Ioan C. Teşu, ‟Simt boala ca iubire a lui Hristos” [‟I feel the illness as God’s love”] (Iaşi: Doxologia, 2017), 271 p. - MORARIU, Maxim (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2020)
Suffering and illness have been, since the first centuries of the Christianity, approached topics. Holy Fathers have tried, based on the Scripture arguments, to define and understand them and to offer keys of seeing them not as punishments, but as a part of the divine pedagogy. Nowadays, when illness has become an often encountered element in almost everybody’s life, the need of approaching this topic again, based on the contemporary realities, but also on Church’s teaching, became imperiously necessary.